MODEL MANAJEMEN SUMBER DAYA PENDIDIKAN ISLAM BERBASIS NILAI DAN TRANSFORMASI DIGITAL: TANTANGAN DAN STRATEGI IMPLEMENTASI - Abdul Azis; Sardimi, Sardimi; Asmawati, Asmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation in education requires Islamic educational institutions to adapt their managerial systems without neglecting Islamic values as their foundational principles. However, previous studies tend to examine Islamic educational resource management and digital transformation separately, resulting in the absence of a systematic integrative model. This article aims to formulate a value-based and digitally integrated model of Islamic educational resource management as a strategic framework to enhance institutional effectiveness and sustainability. This study employs a qualitative approach using library research through thematic analysis of recent literature on Islamic education management and digital transformation. The findings reveal that the proposed integrative model consists of four main dimensions: value dimension (trustworthiness, integrity, and professionalism), strategic managerial dimension (planning, recruitment, development, and evaluation), digital transformation dimension (digital governance and digital literacy), and sustainability and quality dimension. The integration of these dimensions forms an adaptive, value-oriented, and competitive management framework for Islamic educational institutions in the digital era. This model contributes conceptually to the systematic development of Islamic education management aligned with contemporary challenges.